In Vitro Cell Death Determination for Drug Discovery: A Landscape Review of Real Issues. (22nd February 2017) - Méry, Benoite; Guy, Jean-Baptiste; Vallard, Alexis; Espenel, Sophie; Ardail, Dominique; Rodriguez-Lafrasse, Claire; Rancoule, Chloé; Magné, Nicolas
Cell death plays a crucial role for a myriad of physiological processes, and several human diseases such as cancer are characterized by its deregulation. There are many methods available for both quantifying and qualifying the accurate process of cell death which occurs. Choosing the right assay tool is essential to generate meaningful data, provide sufficient information for clinical applications, and understand cell death processes. In vitro cell death assays are important steps in the search for new therapies against cancer as the ultimate goal remains the elaboration of drugs that interfere with specific cell death mechanisms. However, choosing a cell viability or cytotoxicity assay among the many available options is a daunting task. Indeed, cell death can be approached by several viewpoints and require a more holistic approach. This review provides an overview of cell death assays usually used in vitro for assessing cell death so as to elaborate new potential chemotherapeutics and discusses considerations for using each assay.